Rotavirus diarrhea in piglets: A review on epidemiology, genetic diversity and zoonotic risks - MALIK, YASHPAL SINGH; KUMAR, NAVEEN; SHARMA, KULDEEP; SIRCAR, SHUBHANKAR; DHAMA, KULDEEP; BORA, DURLAV PRASAD; DUTTA, TAPAN KUMAR; PRASAD, MINAKSHI; TIWARI, ASHOK KUMAR (The Indian Journal of Animal Sciences, 2014)
Pig farming is considered as backbone of rural poor farmers, belonging to lowest socio-economic strata, where mainly unorganized means of pig farming, improper housing, feeding and management are the constraints, and such practices are well known to expose the pig population to a number of infectious and non-infectious disease causing agents. One among those infectious diseases agents is rotavirus (RV), which is the foremost cause of gastrointestinal infections in mammalian and avian species all over the world, also a predominant cause of enteric infections in pigs, and has potential public health concerns. This review provides information on the frequency of RV infection, genotype diversity and zoonotic potential of its emerging reassortants in Indian porcine population. Prevalence studies done so far revealed gruesomely higher porcine RV prevalence in north-eastern region (46.4%) of India. Analysis of available sequence data of VP7 gene (G genotype) and VP4 gene (P genotype) of porcine group A rotaviruses (Po-RVAs) showed the presence of G4, G6, G9, G12 and P[6], P[7], P[13]and P[19] genotypes. Lately, few of the porcine RV strains also exhibited unique genomic constellations with evidence of interspecies transmission events, mainly involving RV strains of human origin. Evolution of rotaviruses is fast due to point mutation and reassortants generation in case of multiple infections. Thus it is imperative to generate the baseline information for formulating better disease preventive and control strategy. At present, nationwide surveillance and monitoring is prerequisite to assess the distribution of common and unusual genotypes of RVs circulating among pig population in India.